ECONOMICS AND POLITICS OF EUROPEAN INTEGRATION - Berend, T. Iván (Tibor Iván), 1930- author. ([S.l.])
1 online resource
Keywords: The Economics and Politics of European Integration offers a comprehensive history of European integration, from the conceptualization of a United States of Europe, to the present day. The special role of the United States in this process of integration, and the expansion and evolution of the European Union, is critically analyzed. The book also thoroughly discusses the current view of the EU and the complex crises emerging from the COVID-19 pandemic. While the book focuses primarily on Europe, the role of other countries is also examined. The rise of hostile enemies from Turkey, Russia, the US and China is explored,and the history and outcome of Brexit also receives unique focus. Maps are used throughout to clearly depict the enlargement process. This illuminating text will be valuable reading for students and researchers across international economics, economic history, political economy and European studies.